Intelligent Systems Technologies and Applications Volume 2 - Berretti, Stefano; Thampi, Sabu M.; Dasgupta, Soura (Advances in Intelligent Systems and Computing,, 2016)
This book contains a selection of refereed and revised papers from three special tracks: Ad-hoc and Wireless Sensor Networks, Intelligent Distributed Computing and, Business Intelligence and Big Data Analytics originally presented at the International Symposium on Intelligent Systems Technologies and Applications (ISTA), August 10-13, 2015, Kochi, India.  .